Herbivory and parasitic fungi on Empetrum leaves - Olofsson, Johan; Te Beest, Mariska; Ericson, Lars (Dryad Digital Repository, 2013)
This data were collected in the file TimeSeries were collected between 1998 and 2012 and the data in the file Empetrum were collected in 2012 in the Abisko Region in northernmost Sweden (68⁰19’ N, 18. ⁰53’E). Data comes from full-factorial warming-fertilization-herbivore exclusion experiment, where transplants of three forbs were grown for two growing seasons. For detailed methods see Olofsson et al. 2013, Complex biotic interactions drive long-term vegetation dynamics in a subarctic ecostystem. Philosophical Transactions of the Royal Society B, doi: 10.1098/rstb.2012.0486.